Baro-buddies: Supporting the fight against obesity - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
Obesity has reached pandemic proportions across the world. Though novel therapies continue to emerge to promote weight loss, long term maintenance of the lost weight is one of the major challenges in obesity management. A multidisciplinary team approach is often useful in recommending the best patient centric method of losing weight, but this requires constant motivation, guidance, support and need for troubleshooting at times of need. To address this, we propose a new avatar in the obesity management of obesity called the “Baro-Buddy” which is a portmanteau, derived from ‘baros’(weight) and buddy (friend). This brief manuscript describes the eligibility, role and utility of a barobuddy in day-to-day management of obesity. Keywords: Barobuddy, obesity, overweight, peer support, person-centered care Continue..